Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/0310057x0803600504
|View full text |Cite
|
Sign up to set email alerts
|

How Well do Serum sTREM-1 Measurements Prognosticate in Septic Shock?

Abstract: The soluble triggering receptor expressed on myeloid cells (sTREM)-1 has emerged as a potentially useful biomarker for the diagnosis of sepsis. This study aimed to evaluate the prognostic utility of serum sTREM-1 in septic shock, in comparison with that of procalcitonin measurements. Thirty-one consecutive patients in a tertiary medical intensive care unit with septic shock were studied. sTREM-1 levels in blood were measured using a modified immunoblot array technique on days one to three of intensive care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Although sTREM-1 was lower in the cancer group, those patients who died had higher levels. These finding is in accordance with some authors investigating noncancer patients with sepsis [14,16,36,37], and in one retrospective study including patients with chemotherapy-associated febrile neutropenia, higher levels of sTREM-1 demonstrated good correlation with severity and the development of complications [17]. The reduced levels of sTREM-1 found in patients with cancer might be associated with the reduction in total leukocyte and neutrophil counts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although sTREM-1 was lower in the cancer group, those patients who died had higher levels. These finding is in accordance with some authors investigating noncancer patients with sepsis [14,16,36,37], and in one retrospective study including patients with chemotherapy-associated febrile neutropenia, higher levels of sTREM-1 demonstrated good correlation with severity and the development of complications [17]. The reduced levels of sTREM-1 found in patients with cancer might be associated with the reduction in total leukocyte and neutrophil counts.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies including noncancer patients, sTREM-1 showed a strong association with sepsis diagnosis [12,13,16]. Although sTREM-1 was lower in the cancer group, those patients who died had higher levels.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…All these data indicated that strem-1 could serve as an indicator for sepsis prognosis. Some studies failed to find the association between strem-1 and poor outcome [8, 13]. At a cutoff of 252.05 pg/mL, strem-1 measurements yielded a sensitivity of 85.7%, specificity of 75.7%, positive predictive value of 70.6%, negative predictive value of 88.2%, and an accuracy of 79.4% for differentiating nonsurvivors from survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Gibot et al [7] indicated that sTREM-1 was more accurate than PCT and CRP in the diagnosis of sepsis, but others showed that the prognostic utility of serum sTREM-1 in septic shock was inferior to that of PCT [8]. The prognostic value of biomarkers mentioned above for sepsis is unclear.…”
Section: Introductionmentioning
confidence: 99%